A hydrodynamic analysis of swimming propulsion - Schleihauf, R. E. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
The laws that govern propulsion in water are well defined by the established theories of hydrodynamics. However, the application of these theories to specific questions of hand propulsion in swimming is difficult because of a lack of background research data. Inspection of fluid mechanics texts reveals that although highly detailed studies of wings, plates, and other miscellaneous shapes in a fluid flow abound, there is virtually nothing specifically on the hand. To answer the practical questions on hand propulsion in swimming, we must turn to our original background research in biomechanics. Of course, we can fall back on the general theories of hydrodynamics to guide our investigations, and we can use research procedures and conventions consistent with established hydrodynamic theory. However, in the final analysis, this research must be designed to meet the unique requirements of swimming biomechanics. The initial steps in the investigation of hand propulsion in swimming have already been made. Counsilman (1971) revolutionized current thinking on propulsive techniques. His research originated the idea of looking at hand and airfoil motions in analogous terms. Since then, Barthels and Adrian (1975), Rackham (1975), and Schleihauf(1974, 1976, 1977) have generally confirmed the idea that lift as well as drag forces contribute to propulsion. The research that remains to be done is the application of general hydrodynamic theories to specific hand force measurements in swimming. In this paper we approach the problem in two stages. First, we investigate forces on hand models in the fluid lab, using procedures pioneered by aerodynamic researchers. These lab studies generate coefficients of lift and drag values for the hand that will enable us to estimate the size of hand forces produced under a wide range of flow conditions. The second stage of research is to apply pure data from the laboratory to realistic swimming motions. Through motion picture studies key propulsive hand motions are isolated, and the coefficients of lift and drag values are used to predict practical hand force measurements. The techniques for evaluating hand propulsion are similar to those of the aerodynamics engineer, who relies on background aero/hydrodynamic research to calculate wing and propeller forces. A survey of hand force measurements across a sampling of highly skilled competitors allows us to outline the mechanical foundations of propulsion in each of the four competitive strokes. The results of this research offer a detailed and objective technique for evaluating swimming proficiency. We hope that this type of research will help coaches to gain a clearer understanding of effective stroke technique and thereby to direct swimmers with more certainty toward stroke perfection.